Análise do comportamento alimentar, consumo alimentar e estado nutricional de pacientes obesos antes e durante a pandemia por COVID-19 - Souza, Izabelle Caroline Figueiredo (2023)
Introduction: There are countless impacts caused by the pandemic in various spheres of an economic, social, cultural and emotional nature. Studies show that physical inactivity and inappropriate eating behavior during the pandemic increased the risk of obesity in individuals. Objective: To evaluate eating behavior and changes in food consumption and nutritional status of obese people during the COVID-19 pandemic. Methodology: Longitudinal, descriptive study, with retrospective and prospective data. The sample was selected for convenience and consisted of all obese patients assisted by the outpatient clinic of the University Hospital of Sergipe in the period before and during the pandemic. Socioeconomic, lifestyle, anthropometric and eating behavior data were collected, in addition to biochemical and physical activity data, for the latter, the IPAQ was used. Results: 43 patients were evaluated, the majority (88%) female, with a mean age of 44.72±9.17 years. As for socioeconomic data, 58% self-declared brown, married (41.9%), with complete high school (44.2%) and monthly income between 1 and 2 minimum wages (41.2%). When comparing anthropometric data before and during the COVID-19 pandemic, there is a significant gain in weight (p=0.004) and BMI (p=0.002), and body measurements, namely: Arm Circumference (p=0.013), Abdominal Circumference (p=0.024) and Hip Circumference (p=0.001). In the evaluation of eating behavior, on a scale from 0 to 100, Cognitive Restriction was responsible for the highest score (70.67). As for the current practice of physical activity, most were classified as irregularly active (48.86%). The findings point to an increase in health risk behaviors, such as weight gain and worsening eating behavior. Conclusion: The present study demonstrated that the eating behavior with the highest score was Cognitive Restriction and among the changes in food consumption, a reduction in the consumption of red meat and an increase in the consumption of eggs and chicken was evidenced. There was a significant increase in the weight and body measurements of these individuals during the COVID-19 pandemic.